Marked Hyperbilirubinemia Associated with Primary Myelofibrosis Responsive to Ruxolitinib - Sunny Sandhu; Hunza Chaudhry; Sharon Zhang; Devang Prajapati (Case Reports in Hepatology)
Primary myelofibrosis (PMF) is a chronic myeloproliferative disorder seen in older adults which can present both with hepatosplenomegaly as well as mild nonspecific liver enzyme abnormalities. Mild elevations in bilirubin can occasionally be seen due to both intravascular hemolysis as well as extramedullary hematopoiesis. Marked hyperbilirubinemia as a presenting sign of PMF progression, however, has not been reported. We present the case of a patient with a remote diagnosis of PMF, who presented with marked hyperbilirubinemia with a notable response to ruxolitinib.